HPV AWARENESS AND VACCINATION - ARE MEN AND WOMEN EQUALLY AWARE? -A SURVEY AMONG COLLEGE STUDENTS OF JAMSHEDPUR - Kar, Avhipsha; Chakraborty, Oindrila; Dash, Chinmaya; Mukherjee, Sopia (Student's Journal of Health Research Africa, 2024)
Background Human papillomavirus (HPV) is a widespread sexually transmitted infection associated with several cancers. Despite its prevalence, awareness of HPV and its related health implications remains insufficient, particularly among men and younger adults. This study aims to investigate HPV awareness and vaccination coverage among college students in Jamshedpur, with a specific focus on gender disparities. Methods Data were collected from 339 college students using a validated questionnaire that assessed knowledge of HPV, vaccination status, and related attitudes. The study analyzed participants' awareness of HPV and its link to cancer, as well as their vaccination history. Statistical analyses were performed to identify significant differences in awareness and vaccination rates between genders and academic streams. Results The findings revealed moderate awareness of HPV among participants, with 62.8% having heard of the virus and 56.0% recognizing its association with cancer. Women showed significantly higher awareness than men (64.0% vs. 46.0%, p = 0.003) and the availability of the HPV vaccine (63.0% vs. 48.7%, p = 0.024). Vaccination rates were low overall, with only 12.4% of participants reporting vaccination. A notable gender gap in vaccination rates was observed (16.9% of women vs. 6.7% of men, p = 0.008). Conclusion Despite moderate levels of awareness regarding HPV, significant gaps remain, particularly in vaccine uptake and the inclusion of HPV vaccination in national immunization programs. The findings of this study highlight the urgent need for targeted educational initiatives and vaccination campaigns aimed at bridging these knowledge gaps and improving health outcomes related to HPV. Recommendation Future research should explore the underlying barriers to vaccination and further investigate the impact of educational interventions on different demographic groups. By translating awareness into action and ensuring equitable access to immunization, we can make substantial strides in preventing HPV-related diseases and fostering a healthier, more informed population.